MANHAJ KRITIK MATAN ‘Ā’ISYAH RA - Niki Alma Febriana Fauzi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2013)
This paper discussed the methods used by ‘Ā’isyah as benchmark in criticizing matan hadith. The accusation against Islam about the lack of methodology in the study of hadith criticism, especially matan criticism, has forced contemporary Islamic scholars to create a method that can be used to criticize the substance of hadith. Indeed, the principles in criticized matan hadith have been made and used by ‘Ā’isyah. The ‘Ā’isyah manhaj of matan criticism has been tested the reliability. The writer concluded that the methodology of ‘Ā’isyah manhaj of matan criticism was proven reliable for tested the authenticity of hadith by used the correspondence of truth and coherence theories in philosophicalepistemology as the method of analysis.